PERBEDAAN KADAR HEMOGLOBIN (Hb) DALAM DARAH SEBELUM DAN SESUDAH KONSUMSI AIR KELAPA HIJAU (Green Coconut Water) PADA PEKERJA YANG TERPAPAR TIMBAL (Pb) DI KAROSERI X SEMARANG - Qorina Sabila Fa'iza; Onny Setiani; Tri Joko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Paint are one source of exposure lead. Lead used as a pigment in paint. The spray of paint is common in use on various industry, for example, painting car industry. Karoseri industry is the automotive industry engaged of making assemble bus and order, interior furnish, and sell it based of their companies. The study was taken at painting workers because it is often exposed lead from paint that used. Lead coming through the bronchi and the digestive tract could enter blood heme hinder the sites that might reduce the production of hemoglobin blood that led to the emergence of an impairment of health. The purpose of this research is to analyze the difference in the blood levels of hemoglobin before and after water consumption green coconut on workers painting exposed to lead in the karoseri industry. The study including research with the design study quasi experiment that uses one group pre test – post test design. The data collected covering characteristics of respondents (age, discharging personal protective equipment, the activity of smoking, and length of employment), lead in blood levels, and the hemoglobin in blood before and after intervention. Analysis data using the Wilcoxon test shows meaningful differences (p value 0,001) between levels of hemoglobin in blood before and after the consumption of green coconut water. The conclusion is green coconut water able to improved workers who exposed lead industry. Advice for workers in painting, green coconut water good consumed each day during work to reduce the effects of exposure to lead in the blood to improve levels hemoglobin (Hb) in blood and avoid interference effects health.